Revisiting neoliberalism in the age of rising authoritarianisms: Between convictions and contradictions - Emel Akcali (Routledge International Handbook of Global Studies, 2020)
This chapter scrutinizes the conundrum about neoliberalism by exploring the current convictions, contradictions, and ambiguities of ‘actually existing neoliberalism[s]’ (Brenner & Theodore, 2002), or, how their variegated character may lead to or sustain authoritarianism. ‘Actually existing neoliberalism’ reveals that despite having common points of reference, context-specific conditions, experiments, and struggles have meant that neoliberalism has never materialized in any one singular or uniform manner since its instigation in the 1970s (Peck, Theodore, & Brenner, 2009). This compels studying the hybrid character of neoliberalism. Such an analysis can avoid simplistic definitions of neoliberalism by more carefully exploring and comparing context-specific ‘neoliberal’ regulatory experiments. It can also help us better comprehend as such the eruption and the nature of counter-movements around the world that have been launched against the perceived neoliberal order, in variegated and situated ways.